MEASURING THE IMPACT OF SOME ECONOMIC VARIABLES ON THE UNEMPLOYMENT RATE IN IRAQ FOR THE PERIOD (2003- 2020) PREPARATION OF THE TWO RESEARCHERS - M.D .Fareek cheid Matar; M.D. Abdullah Mohammed Rashid (Scholar Express Journals, 2023)
The research dealt with the problem of unemployment in Iraq through a standard analytical study for the period (2003-2020), as unemployment is one of the economic problems that the Iraqi society suffers from, and whose effects are reflected on the economic, social and security situation, and this problem was represented in the increasing rates after the change in 2003 The research measured the effect of some economic variables represented by the following independent variables (inflation rate, economic growth expressed in GDP, population growth rate, total expenditures (current and investment), inflation, population growth rate, number of workers in different sectors (public and mixed). , and private)) on the unemployment rate. The unemployment rate was considered as a dependent variable using multiple regression analysis. According to the results of the standard analysis, the research concluded that there is an inverse relationship between the unemployment rate and the gross domestic product, and this relationship coincides with the logic of economic theory. And the existence of a direct relationship between the rate of unemployment and the rate of inflation, and this also coincides with the logic of economic theory. And the existence of an inverse relationship between the unemployment rate and total expenditures, which also corresponds with economic logic. And the existence of a direct relationship with the unemployment rate and the population, and this corresponds with the economic operative. And the existence of an inverse relationship between the unemployment rate and the number of workers, and this coincides with economic logic as well
Keywords: coincides; variable; existence; unemployment